Microorganisms facilitate uptake of dissolved organic nitrogen by seagrass leaves. Issue 11 (November 2018) - Tarquinio, Flavia; Bourgoure, Jeremy; Koenders, Annette; Laverock, Bonnie; Säwström, Christin; Hyndes, Glenn
Abstract Microorganisms play a critical role in nitrogen cycling by mineralising dissolved organic nitrogen (DON) compounds into bioavailable inorganic forms (DIN). Although DIN is crucial for seagrass growth, the hypothesis that seagrass leaf associated-microorganisms could convert DON to forms available for plant uptake has never been tested. We conducted a laboratory-based experiment in which seagrass (Posidonia sinuosa ) leaves were incubated with15 N-amino acids (aa), with and without associated microorganisms. Samples were collected after 0.5, 2, 6 and 12 h. Both bulk stable isotope and nanoscale secondary ion mass spectrometry (NanoSIMS) analysis showed high accumulation of15 N within seagrass leaf tissues with an associated microbiota, but not in plants devoid of microorganisms. These results significantly change our understanding of the mechanisms of seagrass nitrogen use and provide evidence that seagrass microbiota increase nitrogen availability for uptake by seagrass leaves by mineralising aa, thus enhancing growth and productivity of these important coastal ecosystems.